The Use of E-Portfolio as Innovative Creation of EFL Students in Language Assessment - Syatriana, Eny; Saiful, Saiful; Ariana, Ariana; Dzilarsy, Adni (Universitas Negeri Makassar, 2025)
AbstractThe main aim of this paper is to have an innovative model for helping students to design an e-portfolio assessment subject. This study developed an e-portfolio measurement instrument model, at the individual level of analysis, using responses from 40 e-portfolio student users from the fourth-semester students of Muhammadiyah University, were purposively selected to assess the success of their e-portfolio implementations from their students' perspective. Academic institutions can use the results of this research to assess the success of their e-portfolio implementations from their students’ perspective. It employs the research and development method to collect data, which were used to achieve strengthen confidence in the learning outcomes. Innovative learning is an approach or learning method that uses new, creative ways, prioritizing skills visible in student learning outcomes. Language Assessment and Evaluation courses play an important role in various activities. In terms of the use of e-portfolio for teaching objectives to be achieved, lecturers are required to use interesting methods of e-portfolio implementation teaching assessment and evaluation skills because the results can be used to improve learning outcomes. The findings show that the students' common perceptions of obstacles were inadequate Internet access and trouble adjusting to the e-portfolio. The implementation of the e-portfolio is new, so it is vital to get the opinions of those who use it daily. The paper outlines the advantages and drawbacks of utilizing the e-portfolio as a tool for academic assessment. This will direct scholars and practitioners in the proper implementation of the e-portfolio in higher education establishments